Collagenogenesis in Wounds After Skin Cryodestruction and Introduction of Cryopreserved Cord Blood Serum and Placenta Extract - Kovalov, Gennadiy A.; Ischenko, Iryna O.; Naumova, Olga V.; Dedukh, Ninel V.; Olefirenko, Aleksey A.; Sandomirskiy, Boris P. (Problems of Cryobiology and Cryomedicine, 2017)
The paper is devoted to the study of the effect of cryopreserved cord blood serum (CCBS) and placenta extract (PE) on collagenogenesis in regenerated tissue of skin cold wounds. Polarized light microscopy was used to study the refraction of collagen fibers with types 1 and 3 collagen in the cryogenic thermal wounds of skin after the treatment with either CCBS or PE. It was established that treatment of the animals with cold wounds by intramuscular injection of either CCBS or PE stimulated the formation and remodeling of the fibrous component of extracellular matrix. This effect was manifested in activation of the formation of type 3 collagen with its gradual replacement for type 1 collagen. At the same time, the influence of CCBS was expressed to a greater extent than that of PE. Introduction of CCBS led to an increase in the relative area of type 3 collagen to days 7 and 14 in 4.4 and 2.3 times, respectively, to day 21 it was a 2.1-fold decrease. The presence of type 1 collagens was observed to day 7, to days 14 and 21 the content of mature type 1 collagen exceeded the indices in the control group animals in 15.1 and 2.3 times, respectively. On the 21st day of observation, the relative area of immature type 1 collagen was 4.2-fold increased. Probl Cryobiol Cryomed 2017; 27(2): 133–142